ANALISIS POTENSI LAHAN UNTUK KEBUTUHAN RUANG TERBUKA HIJAU. STUDI KASUS: KECAMATAN KEMBANGAN JAKARTA BARAT - Dharmastyo, Ichsan Adi (Jurnal Planesa (Planologi), 2025)
ABSTRACTAccording to Regulation Number 26 from the year 2007 on Spatial Planning, and Regulation Number 15 from the year 2010 on the Implementation of Spatial Planning, it is mandated that municipal or regional areas allocate 30% of their territory for Green Open Spaces. This allocation should include 20% for Public use and 10% to be administered by private entities. Quantitatively, in the Kembangan District with an administrative area of 2497Ha, there are lands that can be developed into green open space This study employed overlay-intersect analysis using Arc GIS 10.0 to measure the contribution of open land to meeting green open space needs, We used property rights, building use rights, open land distribution. And low building coverage ratio (BCR) area polygons to conclude the potential and contributed land. Results of this study showed that there is 368,19ha of potential land in Kembangan District to be developed as new green space areas. However, due to the building regulation, there is only 93.9 Ha (3.76%) that can be contributed for the new green space development.